Modelo de recuperación de servicios eco sistémicos de regulación y hábitat en la comunidad de Sigchocalle, Provincia de Cotopaxi, periodo 2018 – 2019. - Chisaguano Chisaguano, Fabián Marcelo (2019)
This research was carried out to recover the ecosystem services of regulation and habitats at Sigchocalle community. The study was carried out at Sigchocalle located at the west of Salcedo Canton. Biodiversity has been degraded as a result of human activities with an area of 10.2 h (0.0060% of the total area) in Sigchocalle community. This study area has been altered by human settlements since 1950. Subsequently, after the agrarian reform in 60s-70s, and currently due to the advance of the agricultural frontier, the Andean high mountain (rumi loma). This plan has three action: 1) The current ecosystem characterization services in which delimitation, parcelling and ecological diagnosis were carried out; 2) Design ecological recovery prototypes that include selection of plant species according to the ecosystem services of this small town with native species; and 3) Modeling the recovery of ecosystem services. Through these actions it is intended to reach the original ecosystem. The modeling services recovery was carried out with native species that is an option for sustainable development and conservation of ecosystem services of the Community.